Vivencias de estudiantes universitarios sobre el aprendizaje del idioma inglés - Varela Lescano, Liliana Elizabeth (2019)
ABSTRACT This project research is based on a qualitative study whose main objective is to analyze understandably the English learning experience of students in 4th year of the School of Languages of Universidad Nacional de Trujillo (National University of Trujillo) – 2016. A phenomenological method was applied as a methodological path for qualitative research, based on the German philosopher’s ideas, Martin Heidegger and his book ‘Being and Time’. As a data collection technique was used an exhaust interview to fifteen students chosen randomly. The speech answers were carefully registered to analyze and understand the essence of the phenomenon. At first point of analysis, eight units of meaning were built, then it was followed by a vague and medium analysis; second, still under analysis, eight units of meaning were obtained. The results after an exhausting analysis of each speech were a feeling of frustration due to high expectancy at the beginning of the career in comparison with over the last four years experienced, thus questioning the teaching-learning of the language department. The students feel a lack of interest from teachers to help them face better the problems of the language. In most cases, students depend only on their own effort to keep growing academically.